ESL STUDENTS' INTERPRETATIONS OF PUN IN ENGLISH JOKES - Pasaribu, Tiara Kristina; Pasaribu, Donna Ria; Simanjuntak, Hotnida Irawaty; Hia, Leli Arlinawati; Halawa, Ardiwan (Universitas PGRI Sumatera Barat, 2025)
This research is expected to broaden students' perspectives through humor, specifically